The regulatory and signaling mechanisms of the ASK family. (December 2017) - Nishida, Takuto; Hattori, Kazuki; Watanabe, Kengo
Abstract: Apoptosis signal-regulating kinase 1 (ASK1) was identified as a MAP3K that activates the JNK and p38 pathways, and subsequent studies have reported ASK2 and ASK3 as members of the ASK family. The ASK family is activated by various intrinsic and extrinsic stresses, including oxidative stress, ER stress and osmotic stress. Numerous lines of evidence have revealed that members of the ASK family are critical for signal transduction systems to control a wide range of stress responses such as cell death, differentiation and cytokine induction. In this review, we focus on the precise signaling mechanisms of the ASK family in response to diverse stressors.